Transcrystallization of poly(l-lactic acid) on the surface of reduced graphene oxide fibers. Issue 102 (21st October 2016) - Jing, Mengfan; Jiang, Hong; Guo, Yilan; Wu, Zhiqiang; Fu, Qiang
Abstract : Transcrystalline layer could form between rGOF and PLLA. The good nucleating ability of rGOF could be quantitatively characterized based on the theories of heterogeneous nucleation and crystal growth rate. Abstract : In this work, we investigate the formation process of interfacial crystallization between poly(l -lactic acid) (PLLA) and reduced graphene oxide fibers (rGOFs) using polarized optical microscopy (POM). It was found that the transcrystallization of PLLA on the surface of the rGOF could be achieved and that the degree of transcrystallinity decreased with an increase in crystallization temperature. Micro-Fourier transform infrared spectroscopy (micro-FTIR) and scanning electron microscopy (SEM) were further employed to investigate the molecular chain orientation and internal structure within the interfacial crystalline region. Based on the theory of heterogeneous nucleation and the theory of crystal growth rate, the nucleating ability of the rGOF toward PLLA was evaluated with regards to the value of the interfacial free energy difference function Δ σ . This work is important for the design and fabrication of PLLA/rGOF composites with good interfacial interaction and high-performance.